Predictors of resilience among Indonesian students in Malaysian universities - Khairina; Roslan, Samsilah; Ahmad, Noorlila; Zaremohzzabieh, Zeinab; Mohamad Arsad, Nurazidawati (Faculty of Education, Universiti Teknologi MARA, 2020)
The benefits of internationalization in higher education are indisputable. However, students studying abroad may face difficulties such as adjustment issues since they are away from home and go through a new stage in their lives. Seeing that an essential predictor of psychological adjustment is resilience, the current study aims to assess the role of a range of factors (optimism, social support, selfefficacy, psychological well-being, and demographic) in predicting the resilience of Indonesian students in Malaysia. Two hierarchical multiple regression analyses were used to test the influencing factors on resilience. Based on the literature, this study is quantitative in nature where a total of 229 Indonesian postgraduate students in Malaysian public universities were chosen as participants. Results showed that resilience is affected by optimism, social support, and self-efficacy. Essentially, this study provides practical insights into how international students can make adjustments to reduce the impact of stress faced in challenging situations.